Biomarkers of secondhand smoke exposure in automobiles. Issue 1 (24th January 2013) - Jones, Ian A; St.Helen, Gideon; Meyers, Matthew J; Dempsey, Delia A; Havel, Christopher; Jacob, Peyton; Northcross, Amanda; Hammond, S Katharine; Benowitz, Neal L
Abstract : Objectives: The objectives of this study were: (1) to characterise the exposure of non-smokers exposed to secondhand smoke (SHS) in a vehicle using biomarkers, (2) to describe the time course of the biomarkers over 24 h, and (3) to examine the relationship between tobacco biomarkers and airborne concentrations of SHS markers. Methods: Eight non-smokers were individually exposed to SHS in cars with fully open front windows and closed back windows over an hour from a smoker who smoked three cigarettes at 20 min intervals. The non-smokers sat in the back seat on the passenger side, while the smoker sat in the driver's seat. Plasma cotinine and urine cotinine, 3-hydroxycotinine (3HC) and 4-(methylnitrosoamino)-(3-pyridyl)-1-butanol (NNAL) were compared in samples taken at baseline (BL) and several time-points after exposure. Nicotine, particulate matter (PM2.5 ) and carbon monoxide (CO) were measured inside and outside the vehicle and ventilation rates in the cars were measured. Results: Average plasma cotinine and the molar sum of urine cotinine and 3HC (COT+3HC) increased four-fold, urine cotinine increased six-fold and urine NNAL increased ∼27 times compared to BL biomarker levels. Plasma cotinine, urine COT+3HC and NNAL peaked at 4–8 h post-exposure while urine cotinine peaked within 4 h. Plasma cotinine was significantly correlated to PM2.5 (Spearman correlation rs =0.94) and CO (rs =0.76) but not to air nicotine. The correlations between urine biomarkers, cotinine, COT+3HC and NNAL, and air nicotine, PM2.5 and CO were moderate but non-significant (rs range =  0.31–0.60). Conclusions: Brief SHS exposure in cars resulted in substantial increases in levels of tobacco biomarkers in non-smokers. For optimal characterisation of SHS exposure, tobacco biomarkers should be measured within 4–8 h post-exposure. Additional studies are needed to better describe the relationship between tobacco biomarkers and environmental markers of SHS.